Anti-CD19 chimeric antigen receptor T-cells induce durable remission in relapsed Philadelphia chromosome-positive ALL with T315I mutation. Issue 2 (28th January 2020) - Yang, Fei; Yang, Xiaodong; Bao, Xiebing; Kang, Liqing; Zhou, Lili; Wu, Xiaoxia; Tang, Xiaowen; Fu, Zhengzheng; Ma, Xiao; Sun, Aining; Zhang, Jian; Qiu, Huiying; et al.
Abstract: Effective treatments for relapsed Ph + ALL with T315I mutation are few; CD19 CAR T-cell therapy are a potential therapy for this condition. We reported 7 patients with relapsed Ph + ALL with T315I mutation, who were treated pre- or post-allo-HSCT with CD19-specific CAR T-cells. Of the 7 cases, 6 were in CR or CRp within 1 month after the first infusion of CAR T-cells. MRD revealed a rapid decline in 6 patients. BCR/ABL fusion transcripts were negative in 4/5 cases (not performed in 2). Three patients maintained remission without evidence of MRD by QPCR until the final follow-up, of which 2 received anti-CD19 CAR T-cells and ponatinib at the same time. Our study confirmed the efficacy of anti-CD19 CAR T-cell therapy in treatment of relapsed Ph + ALL with T315I mutation pre- or post-allo-HSCT and the concurrent applicability of this therapy with ponatinib.